(untitled) (CIPEEX, 2025)
Rheumatoid Arthritis (RA) is an autoimmune disease that causes chronic inflammation. Its etiology is multifactorial, involving both genetic and environmental factors. Early diagnosis is essential to avoid irreversible joint damage. Thus, the aim of this study was to review the main aspects related to early RA. A narrative literature review was conducted using the Virtual Health Library (VHL) and Scientific Electronic Library Online (SciELO) databases, including articles published between 2020 and 2024 available in full in English or Portuguese, based on the following keywords: early rheumatoid arthritis, autoimmune disease, and diagnosis. RA is a chronic systemic inflammatory disease of the joints that leads to bone and cartilage destruction. Early diagnosis allows the prevention of irreversible damage related to joint atrophy and loss of movement in the medium and long term. The biomarkers rheumatoid factor and anti-citrullinated peptide antibodies (ACPA) can be used both in diagnosis and prognosis. However, it is concluded that a multidisciplinary approach involving clinical, laboratory, and radiological evaluation is more appropriate, as it allows the disease to be managed in a more detailed and individualized manner, with constant monitoring and minimization of irreversible conditions.